Thermal performance of nanomaterial in solar collector: State-of-play for graphene - Mahamude, Abu Shadate Faisal; Wan Sharuzi, Wan Harun; Kumaran, Kadirgama; Farhana, Kaniz; Ramasamy, D.; Samylingam, L.; Aslfattahi, Navid (Elsevier Ltd, 2021)
Several studies have performed various nanomaterials for the dispersion of working fluids, including copper oxide, alumina, and silica, and so forth in solar collectors. In this present study thermal performance of graphene nanofluid and hybrid, nanofluid has been considered mostly. The thermo-physical properties of the working fluid are significantly enhanced and the performance of solar collectors is therefore improved. This study summarizes the performance of different solar collectors using carbon-based nanofluids especially graphene. The influence of nanofluid concentration, temperature, and flow rate on the collector efficiency of the solar collectors was highlighted. Using graphene thermal conductivity increase by 17% sharp and using graphene derivatives develop almost a 40% increase. Viscosity enhances almost 50% by using graphene nanoparticles. By the way, graphene has stable properties, cheap in price, using a fluid flow mechanism in thermal collector graphene nanoparticles gives an excellent result. The most important and highlighted inherent properties of graphene are its contact angle which is responsible for conductivity. Higher surface area to volume production improves the heat transfer capacity of graphene nanofluids. In this review, the article elaborates on the graphene and graphene-based nanofluid superiority in the thermal solar collector. Graphene nanofluids perform a crucial role in the development of newer technologies ideal for thermal solar systems. This advanced type of graphene nano liquid has a strong potential for use in medium-temperature systems, for example, solar collectors, as innovative heat transfer fluids.